Engineering and entrepreneurship: the experience at Universidad Icesi (2010)
For the last 20 years, the Center for Entrepreneurship Development at Universidad ICESI en in Cali (CDEE-ICESI), Colombia has had experiences in teaching Entrepreneurship Courses that integrated Engineering, Business Economics, and Industrial Design’s students, and. through Wthem we had to develop an integral methodology for our engineering students that solved some of the traditional limitations of the previous professional training. The activities of the Center include many other activities related to entrepreneurship in terms of research and extension, which makes easier the process of motivating and orienting the engineering students to an entrepreneurial career. Some longitudinal studies that we have been done shows that initially (1984-1994) the propensity frequency of business students to startingestablish their own companies was higher than the propensity frequency of the engineering students.; however However, in the last three years we are finding that many of the engineering students are really starting their companies even before they finish their undergraduate studies and in more substantial business which makes us believe that the situation is changing The action of the Center for Entrepreneurship Development has been very important at the regional level because many other universities had takenve adopted our methodology to use it in their courses. , but aAlso, many support mechanism for entrepreneurs and especially for technology based entrepreneurs has been established with our support.